Different extracts of Zingiber officinale decrease Enterococcus faecalis infection in Galleria mellonella - Maekawa, Lilian Eiko [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Barbosa, Júnia Oliveira [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP]; Valera, Marcia Carneiro [UNESP] (FapUNIFESP (SciELO), 2015)
Dried, fresh and glycolic extracts of Zingiber officinale were obtained to evaluate the action against G. mellonella survival assay against Enterococcus faecalis infection. Eighty larvae were divided into: 1) E. faecalis suspension (control); 2) E. faecalis + fresh extract of Z. officinale (FEO); 3) E. faecalis + dried extract of Z. officinale (DEO); 4) E. faecalis + glycolic extract of Z. officinale (GEO); 5) Phosphate buffered saline (PBS). For control group, a 5 μL inoculum of standardized suspension (107 cells/mL) of E. faecalis (ATCC 29212) was injected into the last left proleg of each larva. For the treatment groups, after E. faecalis inoculation, the extracts were also injected, but into the last right proleg. The larvae were stored at 37 °C and the number of dead larvae was recorded daily for 168 h (7 days) to analyze the survival curve. The larvae were considered dead when they did not show any movement after touching. E. faecalis infection led to the death of 85% of the larvae after 168 h. Notwithstanding, in treatment groups with association of extracts, there was an increase in the survival rates of 50% (GEO), 61% (FEO) and 66% (DEO) of the larvae. In all treatment groups, the larvae exhibited a survival increase with statistically significant difference in relation to control group (p=0.0029). There were no statistically significant differences among treatment groups with different extracts (p=0.3859). It may be concluded that the tested extracts showed antimicrobial activity against E. faecalis infection by increasing the survival of Galleria mellonella larvae.

Extratos seco, fresco e glicólico de Zingiber officinale foram obtidos para avaliar suas ações por meio de ensaio de sobrevivência em G. mellonella contra infecção por Enterococcus faecalis. Oitenta larvas foram divididas em: 1) Suspensão de E. faecalis (controle); 2) E. faecalis + extrato fresco de Z. officinale (FEO); 3) E. faecalis + extrato seco de Z. officinale (DEO); 4) E. faecalis + extrato glicólico de Z. officinale (GEO); 5) Solução tampão fosfato salina (PBS). Para o grupo de controle, 5 µL de inóculo de suspensão padronizada (107 células/mL) de E. faecalis (ATCC 29212) foi injetado na última proleg esquerda de cada lagarta. Para os grupos com tratamento, após a injeção de E. faecalis, os extratos foram injetados na última proleg direita. Após as injeções, as lagartas foram armazenadas a 37 °C e o número de animais mortos foi registrado diariamente em 168 h (7 dias) para analisar a curva de sobrevivência. As lagartas foram consideradas mortas quando elas não mostraram qualquer movimento após o toque. A infecção por E. faecalis levou à morte de 85% das lagartas após 168 h. Não obstante, nos grupos de tratamento com associação dos extratos, houve um aumento nas taxas de sobrevivência de 50% (GEO), 61% (FEO) e 66% (DEO) das lagartas. Em todos os grupos com tratamento, as lagartas apresentaram um aumento na sobrevivência, com diferença estatisticamente significativa em relação ao grupo controle (p=0,0029). Não houve diferença estatisticamente significativa entre os tratamentos com os diferentes extratos (p=0,3859). Pode concluir-se que os extratos testados mostraram atividade antimicrobiana contra a infecção por E. faecalis, aumentando a sobrevivência das lagartas de G. mellonella.
Keywords: Enterococcus faecalis; Zingiber officinale; Host-pathogen interactions; Galleria mellonella